Glaucocalyxin A Inhibits the Malignant Progression of Epithelial Ovarian Cancer by Affecting the MicroRNA-374b-5p/HMGB3/Wnt-β-Catenin Pathway Axis - Chen, Feng; Sun, Fang; Liu, Xia; Shao, Jing; Zhang, Bei (Frontiers in Oncology, 2022)
Abstract Objective: Glaucocalyxin A (GLA) is an ent-kaurene diterpenoid from Rabdosia japonica var possessing anti-tumor activity. This study aimed to investigate effects of GLA on epithelial ovarian cancer (EOC) and elucidate underlying mechanisms. Methods: The expression of HMGB3 in EOC tissues was analyzed by GEPIA and immunohistochemistry. Cell proliferation was determined using CCK-8 and colony formation assays. Cell invasion, migration, and apoptosis were detected using Transwell, wound healing, and flow cytometry assays, respectively. Interactions between HMGB3 and miRNAs were predicted using ENCORI and validated using a dual-luciferase assay. mRNA expression levels of HMGB3 and miRNAs were measured using qPCR. Protein expression levels of HMGB3, E-cadherin, N-cadherin, Wnt3a,β-catenin, Bcl-2, and Bax were measured by western blotting. A tumor xenograft model was established to validate the efficacy and mechanism of GLA in vivo. Results: HMGB3 was upregulated in EOC tissues and cells. GLA dose-dependently inhibited EOC cell proliferation and epithelial-mesenchymal transition (EMT). HMGB3 overexpression promoted proliferation, invasion, migration, and EMT, and suppressed the apoptosis of EOC cells. In addition, miR-374b-5p was targeted by HMGB3, and its overexpression hindered malignant characteristics of EOC cells. HMGB3 overexpression weakened antitumor effects of GLA and miR-374b-5p in EOC cells. Moreover, the Wnt-β-catenin pathway was inhibited by the GLA-mediated miR-374b-5p/HMGB3 axis. In vivo experiments showed that GLA inhibited EOC tumor growth, meanwhile, upregulated the miR-374b-5p level and downregulated the expression of HMGB3, Wnt3a, and β-catenin in tumor tissues. Conclusions: GLA suppressed the malignant progression of EOC by regulating the miR-374b-5p/HMGB3/Wnt-β-catenin pathway axis.